(untitled) (Docentes 2.0 Journal, 2018)
The learning experience with teachers shows through theory and practice, the complexity of education and, to a greater degree, difficulty, teacher training. This complexity grows exponentially due to the radical and vertiginous change in the demands of scientific and social organizations. Therefore, the skills and abilities of the teacher in training must go beyond cognitive concepts. It is essential to involve the attitudinal, affective and technological aspects in their activities. The module of update that was applied within the program of Masters in Basic Sciences mention Mathematics, had like purpose to face the participant to his responsibility like educator. The teacher noted that although the university provides the necessary tools to practice the profession, it is in the continuous practice where the challenge and training begins. Consequently, a methodology was proposed that could replicate with their students according to their cognitive load, involving pedagogical, technological and evaluative resources.